2018
DOI: 10.1186/s12860-018-0156-1
|View full text |Cite
|
Sign up to set email alerts
|

Separation of functionally divergent muscle precursor cell populations from porcine juvenile muscles by discontinuous Percoll density gradient centrifugation

Abstract: BackgroundSatellite cells (SC) and their descendants, muscle precursor cells (MPC), play a key role in postnatal muscle development, regeneration, and plasticity. Several studies have provided evidence that SC and MPC represent a heterogeneous population differing in their biochemical and functional properties. The identification and characterization of functionally divergent SC subpopulations should help to reveal the precise involvement of SC/MPC in these myogenic processes. The aim of the present work was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…The isolated muscle stem cells were cultured in MEM-based growth media. Various studies widely used FBS-containing MEM to culture pig muscle stem cells in vitro ( Jeong et al, 2013 ; Miersch et al, 2018 ). Doumit et al, 1993 , showed that pig muscle stem cells had a higher proliferation rate in MEM-based media compared to other media, including McCoy’s 5A, Ham’s F12, DMEM, and DMEM/F12.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolated muscle stem cells were cultured in MEM-based growth media. Various studies widely used FBS-containing MEM to culture pig muscle stem cells in vitro ( Jeong et al, 2013 ; Miersch et al, 2018 ). Doumit et al, 1993 , showed that pig muscle stem cells had a higher proliferation rate in MEM-based media compared to other media, including McCoy’s 5A, Ham’s F12, DMEM, and DMEM/F12.…”
Section: Resultsmentioning
confidence: 99%
“…Cultured meat is an artificial meat that imitates fresh meat using the in vitro production of muscle tissue, which would solve the problems derived from traditional meat production, including animal welfare and environmental pollution ( Post, 2012 ). Various researchers used fetal bovine serum (FBS)-containing minimum essential medium (MEM) to culture pig muscle stem cells for a long time ( Doumit and Merkel, 1992 ; Miersch et al, 2018 ). However, FBS-containing MEM-based culture conditions do not support the stemness of pig muscle stem cells for an extended period.…”
Section: Introductionmentioning
confidence: 99%
“…However, we found a significantly reduced MPC yield in muscles of LBW piglets affecting both cell subpopulations but the negative effect is stronger for the SPS population. SPS cells are thought to form the reserve cell compartment from which SPF cells can be supplied during postnatal growth and thus, are normally characterized by a lower ability to differentiate 36,87 . In our study, expression of MyoG, known to be essential for myoblast differentiation 88 , is increased in SPS cells from LBW piglets.…”
Section: Discussionmentioning
confidence: 99%
“…A highly pure and vital population of satellite cells can be obtained with the established protocol developed in our lab 35 , 36 . Those cells were used to conduct three independent xCELLigence assays, which demonstrated a high repeatability of the cell growth measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that the vast majority of cells isolated with this method are satellite cells that are able to differentiate. Abundance of myogenic markers were demonstrated with flow cytometry and the ability to terminally differentiate and generate myotubes was shown 35 , 36 . For xCELLigence assays (see below), myogenic cells from single animals were seeded in 10 cm collagen-coated culture dishes (Greiner Bio-One, Kremsmünster, Germany) and incubated at 37 °C, 6% CO 2 and 95.5% humidity.…”
Section: Methodsmentioning
confidence: 99%